258 CHANGES IN SYSTOLIC AND DIASTOLIC MYOCARDIAL FUNCTION FOLLOWING LIGATION OF DUCTUS ARTERIOSUS IN PRETERM INFANTS. (10th December 2015) - Noori, S.; Friedlich, P.; Seri, I.
Abstract : Hypothesis: 1) Myocardial function deteriorates due to a sudden increase in afterload following PDA ligation. 2) Myocardial Performance Index (MPI) is a load-dependent measure of cardiac function and therefore MPI would significantly change with ligation of the PDA. Objective: To test these hypotheses by evaluating the changes in systolic and diastolic function following PDA ligation. Methods: In this retrospective study all subjects were referred to the Center for Newborn and Infant Critical Care at Childrens Hospital Los Angeles for PDA ligation during a 9-month period in 2004. We reviewed the clinical data and the echocardiograms performed on each neonate within 6 hours before and immediately after PDA ligation. Assessment of myocardial function included load-dependent measures of contractility such as shortening fraction (SF) and heart-rate corrected velocity of circumferential fiber shortening (VCFc), a load-independent measure of contractility (relation of wall stress [WS] to VCFc), left and right cardiac output (CO), mitral and tricuspid in-flow Doppler, left ventricular tissue Doppler and MPI. Changes in afterload were assessed by measuring wall WS and calculating systemic vascular resistance (SVR). Results: Complete set of data was available in 8 patients that comprised the study group. All data are given as mean±SD. Birth wt 579±16 g, GA 25.6±1 wks, age at ligation 23±13 days. SF decreased from 39±8 to 30±7% (p= 0.01). SVR increased from 109±35 to 206±69 mmHg/ml/kg/min (p= 0.002). There was no change in VCFc (1.35±0.29 vs 1.33±0.42 circ/sec, p=0.4) and WS (17±6 vs 17±10 g/cm2, p=0.4). Left CO decreased from 361±103 to 199±62 ml/kg/min (p=0.001) while right CO did not change (from 395±159 vs 370±140 ml/kg/min (p=0.6). MPI increased from 0.22±0.09 to 0.65±0.27 (p=0.001). Conclusions: 1) There was an acute deterioration in both systolic and diastolic myocardial function immediately following ligation of the PDA. 2) There was a significant change in MPI suggesting load-dependency of this index of myocardial function. Speculation: The right CO did not change secondary to the presence of left to right shunt at the patent foramen ovale.